The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1089/15246090050200060
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Breast Cancer Screening Rates: An Issue of Ethnicity or Socioeconomics?

Abstract: Previous reports suggest that use of preventive measures, such as screening mammography (SM), differs by ethnicity. It is unclear, however, if this is determined directly by ethnicity or indirectly by related socioeconomic factors. We studied self-reported data from 18,245 women aged 40-49 who participated in the Behavioral Risk Factor Surveillance System telephone survey in 1992 and 1993. Of these, 11,509 (63%) reported having obtained mammography within the preceding 2 years for screening purposes only. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 12 publications
4
41
1
Order By: Relevance
“…Analyses of the BRFSS have consistently shown that lack of health insurance is associated with decreased rates of cancer screening. Qureshi et al 6 assessed the effects of insurance status on the likelihood of screening mammography utilization within the preceding 2 years among women ages 40 to 49 using data from the 1992-1993 BRFSS. Separate evaluations of the impact of health insurance on screening mammography utilization were performed for four racial/ethnic groups: non-Hispanic white, non-Hispanic black, Hispanic, and other.…”
Section: Studies Using Data From the Behavioral Risk Factor Surveillamentioning
confidence: 99%
“…Analyses of the BRFSS have consistently shown that lack of health insurance is associated with decreased rates of cancer screening. Qureshi et al 6 assessed the effects of insurance status on the likelihood of screening mammography utilization within the preceding 2 years among women ages 40 to 49 using data from the 1992-1993 BRFSS. Separate evaluations of the impact of health insurance on screening mammography utilization were performed for four racial/ethnic groups: non-Hispanic white, non-Hispanic black, Hispanic, and other.…”
Section: Studies Using Data From the Behavioral Risk Factor Surveillamentioning
confidence: 99%
“…[27][28][29] Access to health care, insurance, and engaging in other healthy behaviors appear to influence a woman' s likelihood of obtaining a screening mammogram. 30 Roberts and Birch 31 found that factors affecting screening include insurance type, provider type, long waiting times, and poor communication among the physician, the staff, and the patient. In another mammography study, significant correlates of utilization included age, household income, and the type of managed care organization in which the member was enrolled.…”
Section: Other Factors Predicting Use Of Screeningmentioning
confidence: 99%
“…Multiple sociodemographic factors affect cancer care patterns, including age, sex, race or ethnicity, insurance status, household income, level of education, and usual source of health care [1][2][3][4][5][6][7][8][9] . Timeliness of care (that is, rapid initiation of treatment after definitive diagnosis) is a key component of high-quality cancer treatment.…”
Section: Introductionmentioning
confidence: 99%